Collagen10a1 GEN EXPRESSION AND BONE MINERALIZATION IN THE col10a1:nlGFP TRANSGENTIC MEDAKA FISH LARVAE - Dinh, Thi Huong; Tran, Duc Long; Pham, Thi Bich; To, Thanh Thuy (Tạp chí Sinh lý học Việt Nam, 2023)
*]:pointer-events-auto R6Vx5W_threadScrollVars scroll-mb-[calc(var(--scroll-root-safe-area-inset-bottom,0px)+var(--thread-response-height))] scroll-mt-[calc(var(--header-height)+min(200px,max(70px,20svh)))]" dir="auto" data-turn-id="request-WEB:35aba3d2-fd98-4613-9705-72e325ca48bf-14" data-turn-id-container="request-WEB:35aba3d2-fd98-4613-9705-72e325ca48bf-14" data-testid="conversation-turn-30" data-turn="assistant"><div class="text-base my-auto mx-auto pb-10 [--thread-content-margin:var(--thread-content-margin-xs,calc(var(--spacing)*4))] @w-sm/main:[--thread-content-margin:var(--thread-content-margin-sm,calc(var(--spacing)*6))] @w-lg/main:[--thread-content-margin:var(--thread-content-margin-lg,calc(var(--spacing)*16))] px-(--thread-content-margin)"><div class="[--thread-content-max-width:40rem] @w-lg/main:[--thread-content-max-width:48rem] mx-auto max-w-(--thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn" data-conversation-screenshot-content=""> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal outline-none keyboard-focused:focus-ring [.text-message+&]:mt-1" dir="auto" tabindex="0" data-message-author-role="assistant" data-message-id="14c4758e-568e-4567-81fc-f8f323c8ea0c" data-message-model-slug="gpt-5-5" data-turn-start-message="true"> Objective: To assess the expression level of the osteoblast-specific collagen10a1 (col10a1) gene and the degree of bone mineralization during the early larval stages of col10a1:nlGFP transgenic medaka fish in order to identify a specific developmental time window suitable for evaluating the bone anabolic effects of bioactive substances. Methods: Homozygous and hemizygous col10a1:nlGFP transgenic medaka larvae at 7, 9, 10, 11, and 14 days post-fertilization (dpf) were included in the study (n = .../group). The larvae were subjected to live staining with Alizarin Red S (ARS) to visualize mineralized bone structures. Fluorescent images were captured using a fluorescence stereomicroscope to record both green fluorescent protein (GFP) and ARS signals. The density of the GFP signal was used to evaluate the expression level of the collagen10a1 gene in osteoblasts, whereas the density of the ARS signal was used to assess the degree of bone mineralization. Signal quantification was performed using ImageJ software. Results: The intensity of the GFP signal increased as the larvae developed from 7 to 9 dpf, followed by a gradual decline from 9 to 14 dpf. Similarly, the intensity of the ARS signal increased from 7 to 10 dpf and then gradually decreased from 10 to 14 dpf. These findings indicate that the optimal developmental window for evaluating the effects of bioactive compounds using a fluorescence stereomicroscope is between 7 and 9 dpf.